EFEKTIVITAS PENERAPAN STRATEGI ACTIVE LEARNING THE POWER OF TWO DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN AL-QUR’AN HADITS DI MADRASAH IBTIDAIYAH - Fadhilatun Ni’mah; Rodliyatin Ni’am; Hisbullah Huda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to examine the effectiveness of the implementation of the power of two type active learning strategy in improving students' critical thinking skills in the subject of Al-Qur'an Hadith. This type of research is a quantitative experiment. This research is a population research with 33 students in class IV. The research instrument consists of a questionnaire on critical thinking ability. The data analysis used used was a prerequisite test consisting of a normality test and a hypothesis test using the ancova test. In the Ancova test, the P value of 0.001 < 0.05 means that H0 is rejected to accept H1 = the TPOT-type active learning learning strategy applied has a significant effect on students' critical thinking skills. in the marginal mean information, the highest mean was obtained, namely the TPOT strategy with a mean value of 85,253 while the conventional strategy was 77,606, so that the TPOT strategy had a significant effect on thinking ability. Further tests using Post Hoc obtained a P value of 0.001, the value is less than 0.05 or less than alpha 5%, so it can be concluded that there is a significant difference in students' critical thinking skills between students who participate in conventional learning and students who participate in learning using the TPOT strategy. The results of the study showed that the power of two type active learning learning strategy could improve the critical thinking skills of grade IV students at MI Miftahul Huda Jenu Tuban.